Analysis of field shaper materials on the deformation behavior of (AA6061) tube in electromagnetic forming process through simulation and experiments. (October 2022) - Soni, Manoj; Ahmed, Meraj; Panthi, Sanjay Kumar; Kumar, Surendra; Gavel, Khushwant Singh
Abstract: Field shaper (FS) is an important tooling of an electromagnetic forming (EMF) systems. Therefore, FS materials and its geometry plays a crucial role in the effective forming and joining process of EMF systems. The materials used to fabricate FS should exhibit high strength and non-magnetic property with good conductivity. The cost of Electromagnetic manufacturing depends on the material of FS. In this study, the effect of various FS materials on process parameters was discussed. Properties such as conductivity, tensile strength and composition of material, were experimentally verified. Comparison of mechanical properties of different FS materials in terms of strength and performance have been analyzed. The electrical parameters, such as the inductance, resistance and Quality factor of FS materials experimentally measured. The factrography analysis of the failure of different FS materials have been carried out and the effect of EMF process parameters and their effect on the deformation of tubular workpiece have been analyzed. Finite element analysis (FEA) analysis was used to validate the experimental results of deformation with simulation to establish performance of FS materials. It was found that CuBe and CuTi alloy can be used as an alternative to Cu for fabricating FS with enhanced durability without compromising its performance.